Identification of thermo-tolerant and thermo-sensitive cucumber genotypes on the basis of morpho-physiological and biochemical markers at seedling stage - Kazimi, Rozina; Hussain, Zahoor; Iqbal, Shahid; Khadija, Faheem; Javed, Muhammad Saleh; Sana, Ahtisham; Safdar, Muhammad; Arooj, Iqra (Journal of Pure and Applied Agriculture, 2025)
Cucumber (Cucumis sativus L.) is the important vegetable crop in Pakistan. Abiotic factors such as water, salt and heat stress reduce its yield. Among these factors, temperature is a vital abiotic factor, which seriously restricts the plant growth and development. The aim of this research was to screen out the thermo-tolerant cucumber genotypes on the basis of morpho-physiological and biochemical markers at seedling stage. It was a pot culture experiment in which seeds of ten different genotypes of cucumber were sown in plastic pots and put in the growth chamber. Six seeds were sown in each pot with three replications. The plants were exposed to three different heat stresses 23°C+2, 40°C+2 and 45 °C ± 2 °C. The thermo-tolerance of selected genotypes was assessed at the seedling stage. In current study, it was concluded that Safoora F1 Hybrid and Fazal F1-Hybrid Cucumber can be categories as heat tolerant, while Khushab Local, Summer Green, Bush Green, C-200, C-400 and Cucumber Desi were regarded as heat sensitive cucumber genotypes at seedling stage because C-200 and Cucumber Desi attained minimum shoot length (0.99 cm, 0.83 cm), shoot fresh weight (9.5 g, 8.06 g), shoot dry weight (0.01 g, 0.03 g), root fresh weight (0.44 g, 0.43 g), root dry weight (0.004 g, 0.001 g), osomatic potential (12.88, 12.54 Ψw), Relative water content (19.87% ,15.99%), stomatal conductance (0.01 mmol m-2 s-1,0.00 mmol m-2 s-1), photosynthesis rate (0.21 μmol CO2 m-2 S-1, 0.00 μmol CO2 m-2 S-1 ), proline contents (4.63 μmol g-1, 4.07 μmol g-1), phospours contents (1.81ppm, 1.08 ppm, and potassium contents (1.52 ppm, 1.03 ppm) at 45°C, respectively. It was concluded that Safoora F1Hybrid and Fazal F1-Hybrid Cucumber can be categories as heat tolerant, while Khushab Local, Summer Green, Bush Green, C-200, C-400 and Cucumber Desi were regarded as heat sensitive cucumber genotypes.